Thermoluminescence dosimetry of mixed neutron – gamma fields (Baghdad Science Journal, 2018)
The method of measurement dosimetry in neutron – gamma field by using CaSo4 : Dy (PTFE) disc which has a diameter of 1.3mm and thickness of 0.2mm and using hydrogenated material as a converters of neutron to recoil protons (n-p) reaction, the discs were irradiated by neutron source (241Am-Be) with flux of 4.5?105 n/cm2s for different time to obtain different dose. The TL signals, which we have been obtained by using the converters, are increases to 71%. So we can resolve the neutron and gamma in mixed field.